Communication Model in Regional-Based Sustainable Waste Management from a Public Health Perspective - Sri Hartati; Dimas Akhsin Azhar; Sena Raselina (Universitas Telkom, 2025)
The gap between the amount of waste input and waste management capacity in a region raises the risk of pollution and impacts public health. The circular economy concept is one of the main strategies in sustainable waste management. This study aims to evaluate and explore waste management actions that have been implemented in the Sumedang region, especially in the Jatinangor area. The study aims to obtain a conceptual model related to communication efforts in waste management that prioritizes sustainable principles while considering the social characteristics of the community in a region or area. This study uses a mixed methods design with a qualitative approach complemented by a quantitative approach within a participatory case study framework. The results of this study indicate that changes in community behavior in waste management can be analyzed by three main factors : attitudes, subjective norms, and perceived behavioral control which are reinforced by perceptions of risks and benefits. Regional social factors such as trust between residents, the influence of local figures, and informal communication shape collective norms through the process of constructing everyday social reality, which ultimately encourages the growth of a circular economy based on participation and adaptive partnerships at the village level. The resulting communication model in waste management demonstrates that waste management at the village level is not merely a technical process, but a social process formed through the construction of meaning, risk perception, and interactions between actors in a regional context. The novelty of this model lies in its holistic and transdisciplinary approach, which combines the dimensions of individual behavior, social networks, and social realities that are continuously negotiated in daily practice.